Ethanol from lignocellulosic biomass: An in-depth analysis of pre-treatment methods, fermentation approaches and detoxification processes. Issue 5 (October 2021) - Devi, Arti; Singh, Anita; Bajar, Somvir; Pant, Deepak; Din, Zaheer Ud
Abstract: Biomass as a resource is present in large quantities and offers environmental benefits from sequestration of carbon to bioenergy production. Production of renewable and sustainable biofuel (bioethanol) from biomass is gaining overwhelming interest globally. Biofuels are important and beneficial from environmental and economic points of view. The gasohol, ethanol blended gasoline, utilization for the transportation sector significantly reduces greenhouse gas (GHG) emissions as well as consumption of fossil fuels. Bioethanol produced from renewable biomass especially lignocellulosic biomass (LCB) provides opportunities for a sustainable, cleaner, environmentally safe, carbon-neutral fuel, and green alternatives for fossil fuel. Although LCB is present in the massive amounts on planet earth, it is not utilized properly for bioethanol production due to many hurdles in the bioconversion process like pretreatment, high cost of enzymes, mixed sugar conversion, fermentation etc. Great efforts have been devoted in technological improvement in the bioconversion process including biotechnological and metabolic engineering fields. This review focuses on the current status, technological advances, and new interventions in the bioconversion process of LCB into bioethanol with special focus on pre-treatment methods, fermentation approaches, and detoxification processes. Graphical Abstract: ga1 Highlights: Lignocellulosic biomass is an excellent resource for bioethanol production. Bioethanol from lignocellulose is a sustainable and renewable energy resource, having potential to fulfill energy demand. Different bioconversion techniques for bioethanol production are evaluated in detail. Detoxification supports to improve the fermentation on enhancing growth of fermentation microorganisms. Future prospects are suggested to overcome the technological barriers in the ethanol production.